G280 Clinical management for senior paediatric trainees – putting theory into practice. (27th April 2015) - Jyothi, S; Kanani, A; Goodyear, H
Abstract : Background: Paediatric trainees have variable training experience in clinical management before they become consultants. While there has been increased awareness in recent years of the need to incorporate this into training, there is no agreed way across all deaneries. Aims: To pilot a clinical management course for level 3 trainees (ST6–8) in our deanery with the help of Keele University for 2 years (2012–14). To survey other deaneries on clinical management training for level 3 paediatric trainees. Methods: We drew up a 4 day paediatric bespoke clinical management course with Keele University in 2012. The main course topics were history and structure of the NHS, financing healthcare, personality types, leading and motivating teams, leadership style and handling conflict, writing a successful business case and the basics of service improvement projects (SIPS). All attendees were expected to complete a SIP and present it to their group on the last day. We reviewed feedback after 2 cohorts of trainees (total 42) completed the course. An email questionnaire was sent to all paediatric Head of Schools (HOSs) in October 2014. Results: Feedback for our course was consistently positive and all trainees felt they gained insight into topics that are not usually covered during their training. They appreciated the main course topics. We received 7 replies to our email questionnaire. 6/7 deaneries allocated an annual £400–£600 study leave budget per senior trainee including life support courses. 4 deaneries provided management courses combined with other specialties but the trainees were not expected to complete SIPs. 3 deaneries did not offer formal course on management. Conclusions: After review of feedback, we made a few modifications and have decided to run this course yearly for the next 5 years. A structured clinical management programme by deaneries would improve knowledge and confidence amongst trainees to help lead changes in the future.